Consensus-based recommendations of Australian podiatrists for the prescription of foot orthoses for symptomatic flexible pes planus in adults - Banwell, Helen A (J Foot Ankle Res, 2014)
BACKGROUND: Foot orthoses are commonly used for symptomatic flexible pes planus in adults. However, there are no clinical guidelines for the prescription of customised foot orthoses that are specific to this population. The aim of this study was to investigate prescription habits of Australian podiatrists for customised foot orthoses for symptomatic flexible pes planus in adults and to develop consensus-based practice recommendations for the prescription of these foot orthoses. METHODS: A four round Delphi survey was undertaken with 24 podiatric experts to establish current use and rationale for individual prescription variables of customised foot orthoses for symptomatic flexible pes planus in adults. Round one determined prescription use (consensus) and rounds two, three and four determined the rationale for use (agreement) of prescription variables across the rearfoot, midfoot, forefoot, as well as accommodation and materials used. For consensus and agreement to be accepted, 70% of the respondents were required to use or agree on the rationale for use of individual prescription variables. RESULTS: Consensus was reached in round one for two variables, choice of shell material (polyolefin) and when to prescribe a forefoot post balanced to perpendicular. In rounds two, three and four, agreement was reached for 52 statements related to the rationale for use of individual prescription variables, including when to prescribe: an inverted cast pour [heel in an inverted position], an inverted rearfoot post, a medial heel (Kirby) skive, minimal/maximum arch fill, a medial flange, a forefoot post and common orthotic accommodations. CONCLUSION: This study found consensus or agreement for the use of several prescription variables for customised foot orthoses for symptomatic flexible pes planus in adults. The findings were used to develop the Foot orthosis Prescription Recommendations for symptOmatic flexible Pes planus in adults (FootPROP) proforma, to guide clinicians and researchers in the prescription of customised foot orthoses for this population. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13047-014-0049-2) contains supplementary material, which is available to authorized users.